The influence of Exemplary Leaders, Non-Physical Environment and Reward to Work Discipline (Case Study on PT Apparel One Indonesia 2) - Qurniati - Qurniati; Rara Ririn Budi Utaminingtyas; Endang - Sulistiyani (Politeknik Negeri Semarang, 2020)
This study aims to find out the partial and together influence variables of exemplary leaders, non-physical work environment, and reward for employee work discipline at PT X. The data collection method in this study uses questionnaires and literature study. The sampling method used was a purposive sampling technique and the sample of this study was 95 employees of the PT Apparel One Indonesia production 2. The data analysis technique used was multiple regressions. From this multiple analysis, it can be found that the exemplary leaders, non-physical work environment, and reward affect employee work discipline. The results of the coefficient of determination (Adjusted R Square) shows that the exemplary leaders, non-physical work environment, and reward affect work discipline by 40.3%, while 59.7% is explained by other factors not examined in this study. The most dominant variable influencing works discipline is the reward, then the exemplary leaders and finally the non-physical work environment.